Virtual HIV pre-exposure prophylaxis outpatient service in the era of COVID-19. (January 2021) - Quirke, Siobhan; Quinn, Laura; Hegarty, Deborah; Loy, Aisling; Lyons, Fiona; Mulcahy, Fiona; Devitt, Emma
In the midst of the COVID-19 pandemic, health care providers have had to rapidly change how they deliver care to patients. We discuss how we are delivering a virtual HIV pre-exposure prophylaxis (PrEP) service during this time; challenges faced; challenges expected and goals for the coming months.